A new leafhopper genus and two new species of the tribe Scaphytopiini (Hemiptera: Cicadellidae: Deltocephalinae) from China - Duan, Yani; Zhang, Yalin (Zootaxa, 2013)
New leafhopper taxa in the deltocephaline tribe Scaphytopiini Oman are described: Xenovarta lui sp. n., and a new genus and species Aparaphysis lushuiiensis, gen. n., sp. n. from China. Detailed morphological descriptions and illustrations of the new genus and species are given. A checklist to genera of Scaphytopiini is provided.